Prognostic impact of bone marrow fibrosis in primary myelofibrosis. A study of the AGIMM group on 490 patients. Issue 9 (4th July 2016) - Guglielmelli, Paola; Rotunno, Giada; Pacilli, Annalisa; Rumi, Elisa; Rosti, Vittorio; Delaini, Federica; Maffioli, Margherita; Fanelli, Tiziana; Pancrazzi, Alessandro; Pieri, Lisa; Fjerza, Rajmonda; Pietra, Daniela; et al.
Abstract : The prognostic significance of bone marrow (BM) fibrosis grade in patients with primary myelofibrosis (PMF) is still debated. A fibrosis grade greater than 1 was shown to associate with higher risk of death, and addition of fibrosis grade to IPSS score resulted in a more accurate prediction of survival. The aim of this study was to analyze the prognostic impact of BM fibrosis in 490 patients with PMF, evaluated at diagnosis, molecularly annotated and with extensive follow‐up information. We found that fibrosis grade 2 and greater on a 0–3 scale was associated with clinical characteristics indicative of a more advanced disease, such as anemia, leukopenia, thrombocytopenia, constitutional symptoms, larger splenomegaly and a higher IPSS risk category. Patients with higher grade of fibrosis were also more likely to have additional somatic mutations in ASXL1 and EZH2, that are prognostically adverse. Median survival was significantly reduced in patients with grade 2 and 3 fibrosis as compared with grade 1; this effect was maintained when analysis was restricted to younger patients. In multivariate analysis, fibrosis grade independently predicted for survival regardless of IPSS variables and mutational status; the adverse impact of fibrosis was noticeable especially in lower IPSS risk categories. Overall, results indicate that higher grades of fibrosis correlate with unique clinical and molecular aspects and represent an independent adverse variable in patients with PMF; these observations deserve confirmation in prospectively designed series of patients. Am. J. Hematol. 91:918–922, 2016. © 2016 Wiley Periodicals, Inc.